Vanadium Induces Oxidative Stress and Mitochondrial Quality Control Disorder in the Heart of Ducks - Xiong, Zhiwei; Xing, Chenghong; Xu, Tianfang; Yang, Yan; Liu, Guohui; Hu, Guoliang; Cao, Huabin; Zhang, Caiying; Guo, Xiaoquan; Yang, Fan (Frontiers in Veterinary Science, 2021)
Vanadium (V) is an ultra-trace element presenting in humans and animals, but excessive V can cause toxic effects. Mitochondrial quality control (MQC) is an essential process for maintaining mitochondrial functions, but the relationship between V toxicity and MQC is unclear. To investigate the effects of excessive V on oxidative stress and MQC in duck hearts, 72 ducks were randomly divided into two groups, including the control group and the V group (30 mg of V/kg dry matter). The cardiac tissues were collected for the histomorphology observation and oxidative stress status evaluation at 22 and 44 days. In addition, the mRNA and protein levels of MQC-related factors were also analyzed. The results showed that excessive V could trigger vacuolar degeneration, granular degeneration, as well as mitochondrial vacuolization and swelling in myocardial cells. In addition, CAT activity was elevated in two time points, while T-SOD activity was increased in 22 days but decreased in 44 days after V treatment. Meanwhile, excessive V intake could also increase the number of Drp1 puncta, the mRNA levels of mitochondrial fission–related factors (Drp1and MFF), and protein (MFF) level, but decrease the number of Parkin puncta and the mitochondrial biogenesis (PGC-1α, NRF-1, and TFAM), mitochondrial fusion (OPA1, Mfn1, and Mfn2), and mitophagy (Parkin, PINK1, P62, and LC3B) related mRNA levels and protein (PGC-1α, Mfn1, Mfn2, PINK1) levels. Collectively, our results suggested that excessive V could induce oxidative stress and MQC disorder in the heart of ducks.